2011
DOI: 10.5586/asbp.2007.002
|View full text |Cite
|
Sign up to set email alerts
|

Localizatlon of expansin-like protein in apoplast of pea (Pisum sativum L.) root nodules during interaction with Rhizobium leguminosarum bv. viciae

Abstract: During nodule development on pea roots, apoplast undergoes changes in activity of plant cell wall proteins such as expansins (EXPs). Because the accumulation of EXP protein has been correlated with the growth of various plant organs, we investigated using Western Blot and immunolocalization studies with antibody against PsEXP1, whether this protein was accumulated in the expanding cells of nodule. Immunoblot results indicated the presence of a 30-kDa band specific for pea root nodules. The EXP proteins content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Expansin proteins have been found in the nodule apoplast as well as in infection thread walls (Sujkowska et al, 2007). Nitrogen-fixing symbiosis (NFS) and AM share a common signal transduction pathway, as microorganisms transfer mineral nutrients to the host plant in both associations, and in both associations the microorganisms are isolated from the host cytoplasm by the apoplastic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Expansin proteins have been found in the nodule apoplast as well as in infection thread walls (Sujkowska et al, 2007). Nitrogen-fixing symbiosis (NFS) and AM share a common signal transduction pathway, as microorganisms transfer mineral nutrients to the host plant in both associations, and in both associations the microorganisms are isolated from the host cytoplasm by the apoplastic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of a sweet clover (Melilotus alba) α-expansin gene, MaEXP1, is enhanced within hours of rhizobial infection, and MaEXP1 also is expressed in the nodule cortex, meristem, invasion zone, and interzone II-III (Giordano and Hirsch, 2004). Western-blot analysis revealed that an expansin-like protein, PsEXP1, is localized in IT walls of pea nodules (Sujkowska et al, 2007), suggesting that PsEXP1 might function in IT growth. More recently, a β-expansin gene, GmEXPB2, was found to be critical for soybean nodulation (Li et al, 2015).…”
Section: Increasing Nodule Size1 Expression Is Required For Normal Rhmentioning
confidence: 99%
“…In roots of white sweet clover (Melilotus alba), the mRNA accumulation of a sweetclover a-expansin gene (MaEXP1) was enhanced within hours of rhizobial inoculation, and the transcript of MaEXP1 was also present in nodule cortex and meristem cells, the invasion zone, and interzone II-III (Giordano and Hirsch, 2004). In pea, western-blot analysis revealed that an expansinlike protein, PsEXP1, was localized in nodule apoplasts and IT walls, suggesting that PsEXP1 might be required for nodule cell and IT growth (Sujkowska et al, 2007). Although transcriptional analysis of genes involved in soybean nodulation have been carried out (Carvalho et al, 2013), details of gene functions during nodulation remain poorly understood.…”
mentioning
confidence: 99%